Training on Optimizing the Potential of Fresh Goat Milk into Cheese at Arjuna Farm - Agung Pratama; Juli Novita Sari; Zikri Noer; Marina Wulandari Nasution; Dona Tiara Lubis (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Arjuna Farm Sheep and Goat Farm produces goat milk products. Goat milk can be processed into various products, one of them is cheese. This community service activity through training in making cheese products from goat milk aims to provide assistance to farmers with a focus on processing fresh goat milk into quality cheese at Arjuna Farm. Cheese has a longer shelf life than milk. By turning milk into cheese, farms can extend the shelf life of their products. The problems identified include low knowledge and skills of farmers and limited access to appropriate materials and equipment. To overcome these problems, this activity offers several solutions, including training and workshops to improve farmers' knowledge and skills for making cheese from goat milk, direct assistance in the cheese processing process, and provision of simple materials and equipment. So that Arjuna Farm not only sells goat milk, but can also produce cheese and can reach a wider market segment. The methods used in this community service are training and practice, guidance, and monitoring and evaluation.